A Multi-Keyword Ranked Search Method On Encrypted Data Using Symmetric Encryption Over Cloud - Rani, Poonam (International Journal of Psychosocial Rehabilitation, 2019)
Data security and privacy have grown to be key concerns as cloud computing usage increases. It is difficult to do effective keyword-based searches on encrypted data kept in the cloud due to the inherent tension between searchability and confidentiality. This study suggests a brand-new multi-keyword ranked search methodology that permits effective searching on material that has been encrypted with symmetric encryption methods. The suggested approach guarantees data privacy while enabling users to get appropriate search results based on a variety of terms. To protect data privacy and accomplish effective search operations, the method makes use of secure encryption techniques and index creation methods. Experimental findings show that the suggested strategy is successful and efficient.